BRONŞİYOLİTİS OBLİTERANS ORGANİZE PNÖMONİ (BOOP): Bir Olgu Sunumu - SİPAHİ, Sevtap and BİLİR, Muammer and; YEL, Tuncer and; RCİ, Sabriye and ÖZ, Büge (Cerrahpaşa Medical Journal, 2014)
Background. Bronchiolitis is an inflammatory process that primarily affects the small conducting airways of the lung. BOOP is a nonspecific pattern with different causes or associations; including a variety of infections fume exposures, drugs, and collagen diseases. No etiology is found in a number of cases, which are then termed idiopathic. The diagnostic distinction is important, because patients with idiopathic BOOP have a favorable prognosis and response to steroid therapy. Observation. The clinical course of a 62 year old male patient with complaints of productive cough and dyspnea diagnosed histopathologically as idiopathic BOOP by open lung biopsy is presented.